A Multi-Center Study on the Relationship Between Developmental Regression and Disease Severity in Children With Autism Spectrum Disorders - Hu, Chaoqun; Yang, Fan; Yang, Ting; Chen, Jie; Dai, Ying; Jia, Feiyong; Wu, Lijie; Hao, Yan; Li, Ling; Zhang, Jie; Ke, Xiaoyan; Yi, Mingji; et al. (Frontiers in Psychiatry, 2022)
Introduction: This study aimed to investigate the prevalence of developmental regression in children with Autism Spectrum Disorder (ASD) and to explore its relationship with disease severity. Methods: We finally included 1027 ASD children aged 2-5 years from 13 cities in China: 138 with regressive ASD and 889 with non-regressive ASD. The Social Responsiveness Scale (SRS), Autism Behavior Checklist (ABC), Child Autism Rating Scale (CARS), Children Neuropsychological and Behavioral Scale-Revision 2016 (CNBS-R2016) were used to evaluate the core symptoms and developmental status of children in the two groups. Results: Among the 1027 ASD children eventually included, 138 (13.44%) cases showed regressive behavior and the average regression occurring age was 24.00(18.00-27.00) months. Among the regressive children, 105 cases (76.09%) had language regression, 79 cases (57.25%) had social regression, and 4 cases (2.90%) had motor regression. The total scores of ABC and the sub-score of sensory and stereotypic behavior (β=5.122, 95% CI: 0.818, 9.426, P<0.05; β=1.104, 95% CI: 0.120, 2.089, P<0.05; β=1.388, 95% CI: 0.038, 2.737, P<0.05), the SRS total scores and the sub-score of autistic mannerisms (β=4.991, 95% CI: 0.494, 9.487, P<0.05; β=1.297, 95% CI: 0.140，2.453, P<0.05) of children in the regressive group were all higher than the non-regressive group. The total developmental quotient (DQ) of CNBS-R2016 and the DQ of gross motor, fine motor, adaptive behavior, language (β=-5.827, 95% CI: -11.529, -0.125, P<0.05) and personal society in the regressive group were lower than the non-regressive group and the proportion of children with intelligent developmental impairment was higher the non-regressive group. Conclusion: Regressive autism is mainly manifested as language and social regression. Children with regressive ASD have more severe core symptoms, lower neurodevelopmental level DQ, and more serious disease degree than children with non-regressive ASD, which requires further etiological examinations and more clinical attention.